Testing XRF Discrimination of Marine and Terrestrial Flood Deposits in Southeastern Texas Coastal Marshes - Williams, Harry F.L; Liu, Kam-biu (Journal of coastal research, 2021)
Williams, H.F.L. and Liu, K.-b., 2021. Testing XRF discrimination of marine and terrestrial flood deposits in southeastern Texas coastal marshes. Journal of Coastal Research, 37(6), 1081–1087. Coconut Creek (Florida), ISSN 0749-0208. This study tests the ability of X-ray fluorescence (XRF) analysis to discriminate between storm-generated marine and terrestrial sediment beds in coastal wetlands. Cluster analysis was applied to the elemental compositions of a sediment core and a monolith collected from McFaddin National Wildlife Refuge in southeastern Texas. The core contains washover sediment beds previously attributed to hurricanes Ike, Rita, Carla, and Audrey. The monolith contains a terrestrial flood deposit attributed to Hurricane Harvey and a washover sediment bed attributed to Hurricane Ike. Clustering correctly distinguished between washover, flood, and marsh deposits. This level of discrimination was not achieved by previous studies based on loss-on-ignition and microfossil analyses because sediment from these different sources can have similar moisture, organic, carbonate, texture, and microfossil characteristics. Cluster analysis places every centimeter of a sediment core into a cluster, providing a more precise means of evaluating the relative contributions of marine and terrestrial sources. In the study area, for example, cluster analysis suggests that 50.5% of coastal marsh sediment was derived from marine sources. The XRF technique used in this study is a promising tool for discrimination of marine and terrestrial sediment sources. Further research is warranted to apply this technique in other coastal environments subject to marine and terrestrial sediment inputs.